Tantangan dan Upaya Guru PAI dalam Perubahan Era Globalisasi Revolusi Industi 4.0 di SMP NU Babakan Gebang - Sulaiman, Sulaiman; Maulana, Mohamad Ikhwan; Amirudin, Amirudin (Lembaga Publikasi Ilmiah Universitas Islam Bunga Bangsa Cirebon, 2023)
In this era of globalization and information, teachers are challenged by the behavior of students who like to surf in cyberspace through android, gadgets or sophisticated mobile phones that they have. This student behavior is marked by the tendency to prefer reading through mobile phones rather than books, like to look for various information on their own without checking first, like to find friends through social media accounts, and seem individualistic. For this reason, teachers in learning must be able to utilize information technology. This research method uses a qualitative research method that aims to determine the level of teacher readiness, the challenges faced, and the strategies carried out by teachers in facing the era of the Industrial Revolution 4.0. From the results of the above research, the author concludes that the challenges of Islamic Religious Education teachers in the era of the industrial revolution 4.0, are that teachers must be literate in digitization and be able to compete in the problem of teaching and learning changes that are developing every year to improve the system and learning environment in the classroom.Keyword: PAI Teacher Challenges; PAI Teacher Efforts; Industry 4.0 Revolution.